Accelerators, Amplifiers, and Conductors: A Model of Tertiary Deviance in Online White Supremacist Networks. Issue 7 (2nd July 2020) - Gottschalk, Simon
ABSTRACT: As recent perpetrators of racially-motivated mass-shootings were visitors and contributors to online white supremacist networks, this article presents a preliminary model that attempts to understand the social psychological effects of interacting in these networks. Combining Jonathan Turner's theory of the social psychological roots of extreme violence, scholarship on the white supremacist movement, and research on computer-mediated communication, it suggests that interactions in online white supremacist networks accelerate the conversion from secondary to tertiary deviance, amplify the negative emotional energy released by this conversion, and, under certain conditions, transform this energy into a violent kinetic force. The model is not unique to online white supremacist networks and will hopefully guide research in other types of networks as well.